A Multidimensional Understanding of the Relationship between Sexual Identity, Heteronormativity, and Sexual Satisfaction among a Cisgender Sample - Brad van Eeden-Moorefield; Steph Cooke; Jacqueline Bible; Elvis Gyan (Social Sciences, 2023)
Contemporary scholarship has begun to focus more on understanding the myriad health disparities (e.g., sexual anxiety, depression) related to sexual identity and its correlates. Sexual satisfaction is linked to many of these disparities, thereby serving as a potentially impactful correlate to understand more deeply in ways that might suggest potential intervention sites to mitigate various disparities. Further, there have also been calls to consider sexual identity multidimensionally beyond only self-identified sexual orientation (LGBQ+ vs. heterosexual) as well as to better understand the role of cultural factors, such as heteronormativity, as correlates of health disparities. Accordingly, this cross-sectional study used internet survey data from 455 cisgender adults of varying sexual identities to test a moderated mediating model linking two dimensions of sexual identity (self-identified sexual orientation and attraction) to sexual satisfaction as mediated by heteronormativity. Results from the multi-group path model analysis were significant for moderation and suggest that heteronormativity mediated the relationship between the attraction dimension of sexual identity and sexual satisfaction only for those who identified as queer (i.e., LGBQ+), whereas attraction was directly related to sexual satisfaction for those that self-identified as heterosexual. Thus, different dimensions of sexual identity have differential impacts on sexual satisfaction and negative impacts of heteronormativity appear significant only for those that identify as queer.